Reference Value Oriented Analysis for Counseling Program Development in Facilitating Vocational Identity Formation of Prospective Counselor - Ilfiandra, Ilfiandra; Akhmad, Sudaryat Nurdin (Universitas Muhammadiyah Metro, 2021)
This study examines the issue of reference value-oriented analysis for counseling program development in facilitating the identity formation of prospective counselors. The special purpose of the study is to map the students' reference value orientations and vocational identity status. The study design used in this research is a cross-sectional survey. The subject of study is 81 psychology department of education and counseling students who are proportional randomly selected based on their class and sex. Reference value orientation instrument is used as a means of collecting data refers to Spranger theory, IONIR models, which developed by Kartadinata (1998). Vocational identity status instruments refer to the concept of Marcia to measure the manner or style in facing identity issues which are based on high or low exploration and commitment in using vocational domain and Adolescence's Vocational Identity : adaptation of the Occupational Identity Scale (OIS), which is developed by Feliciano H Veiga and Helia Moura (2005). The study shows that students' value orientation reference is spread on a wide range of values. Orientation priority lies in the economic, scientific, social, and religious. Meanwhile, based on active status, student vocational identity is also still spread with the greatest proportion of the low-status identity. Students who have high identity status at the beginning tend to be oriented on the value of themselves as individuals, then human values as a society. On the contrary, students who have lower status prefer identity value associated with human beings as members of society than oriented human value as an individual.